Theological discourse of jihad operations of terrorism actions in Indonesia - Abdul Jamil Wahab; Muhammad Ishom; Anik Farida; Zulkarnain Yani; Retno Kartini Savitaningrum Imansah; Basori (Cogent Social Sciences, 2025)
Numerous studies were conducted on terrorism by various scholars in Indonesia, whose perpetrators defined the act as jihad, and targeted the opposing group, namely the infidels. This understanding is the basis for justifying their acts of terrorism. This is different from several scholars stated that the law of jihad should not be carried out without a clear underlying reason. Therefore, Therefore, an in-depth study of the law of jihad in terrorist operations is needed. This study explained the four legal issues in jihad operations to fill the void and preliminary complement. Data were collected from the opinions of scholars written in various literatures through contextualization and manhaji in the social fiqh method. The results showed, first, the original law of jihad is defensive warfare and kifaya obligation, not aini, as stated in current jihadist propaganda with certain conditions justified by religion. Second, war against civilians were not justified, because the existence of non-Muslims as civilians had rights that must be guaranteed by the government. Third, jihad does not target police institutions (al-syurthah) that enforced amar ma’ruf and nahi munkar. The police are a tool for state leaders to create order and security for the people. Fourth, suicide bombing is prohibited, because authority must be provided by a legitimate government that had declared a state of war emergency. The results showed that Islam does not condone violence and the results of this study can be used as a counter-narrative to the propaganda of terrorism widely developed in Indonesia.